To Lessen Repression and Depression: The Relationship Between Sexual Repression and Mental Health Among Lesbian, Gay, Bisexual, Transgender, and Queer Individuals - Jacobson, Ariele (Université Saint-Paul / Saint Paul University, 2018)
While many researchers have studied the specific struggles of members of the gay, lesbian, bisexual, transgender, queer (LGBTQ+) community, sexual repression has not been mentioned in the literature. This paper summarizes the results of a qualitative research with ten participants, who identified as members of the LGBTQ+ community, and who shared their experiences surrounding sexual repression. It analyzes sexual repression as defined by Sigmund Freud and applies it to the struggles of LGBTQ+ individuals in Ottawa, Ontario. More specifically, this paper examines the factors that participants believe lead to and maintain sexual repression and how they perceive that this impacts the mental health of the people who suffer from it. The main themes that arose during this research were as follows: misconceptions held by others, including expectations, rules, and objectifications; stigma; belonging, acceptance, and sense of community; internalized view of self and emotional / mental impact; safety, including implications of disclosure and safe spaces; and attitudes about sex and the self as a sexual / gendered being. The participants explained how they perceive that these factors have led to and maintained sexual repression at different points in their lives and how they believe that they have influenced their mental health.
Keywords: sexual; repression; sexuality; LGBTQ+